Zur Krise der menschlichen Selbsterkenntnis: Hegel und Menke über Bildung und Befreiung (Revista Eletrônica Estudos Hegelianos, 2024)
This text tries to investigate the relationship between Bildung and liberation. According to a certain Hegelianism Bildung is mainly characterized as the acquiring of a second nature or habit. This means that the subject of Bildung has to undergo a metaphysical transformation with the end of becoming a rational being. As second nature our rational capacities are supposed to be free and unfree at the same time. I want to argue that this is not what Hegel has in mind when he thinks about the relation between Bildung and freedom. Rather this reading is the result of a confusion about the role of habit in subjective spirit and objective spirit. In contrast I want to argue that if this Hegelianism is right, we couldn’t comprehend the very possibility of our freedom. Instead, Hegel wants to show us that the very idea of a metaphysical transformation rests upon the assumption that the learning subject does something different than the teaching subject. However, if we want to make sense of the idea of Bildung we must conceive it as a process in which the learning and the teaching subject perform the same activity on different levels of perfection. Only then can we understand the unity of the act that is Bildung.